Active intermediates in heme mono reactions as revealed by cryoreduction/annealing, EPR/ENDOR studies - Davydov, Roman (2010)
This review describes the use of cryoreduction/annealing EPR/ENDOR techniques for determining the active oxidizing species in reactions catalyzed by heme monooxygenases. The three candidate heme states are: ferric peroxo, ferric hydroperoxo, and Compound I intermediates. The enzymes discussed include cytochromes P450, nitric oxide synthase and heme oxygenase.